Timing for Pacing after Acquired Conduction Disease in the Setting of Endocarditis - Daniel Brancheau; George Degheim; Christian Machado (Case Reports in Cardiology)
A 53-year-old gentleman with a history of a mechanical aortic valve presented to the emergency department complaining of a sudden right-sided abdominal pain. He was found to have atrioventricular dissociation on his initial electrocardiogram and his blood cultures grew Streptococcus viridans. The suspicion for endocarditis with periaortic abscess was high so a transthoracic echocardiogram was performed and showed a mass in the left ventricular outflow tract. For better visualization, a transesophageal echocardiogram was recommended and revealed a bileaflet mechanical aortic valve with perivalvular abscess and valvular vegetation as well as severe eccentric paravalvular aortic regurgitation. After sterilization, the patient underwent a successful surgery. Postoperatively, he remained in complete heart block and a permanent pacemaker placement was performed after complete sterilization. He tolerated the procedure well and was discharged home in a stable condition. Perivalvular abscess is one of the most common cardiac complications of infective endocarditis and is associated with an increased risk of mortality. It is imperative to have appropriate treatment guidelines established. However, because of the relative nature of the disease process and the acuity at which intervention needs to be done, a true assessment of the duration of antibiotic therapy prior to surgical intervention, timing of pacemaker placement, and the type of pacemaker is controversial.